Environmental Endocrine-Disrupting Chemical Exposure: Role in Non-Communicable Diseases - Kumar, Manoj; Sarma, Devojit Kumar; Shubham, Swasti; Kumawat, Manoj; Verma, Vinod; Prakash, Anil; Tiwari, Rajnarayan (Frontiers in Public Health, 2020)
The exponential growth of pollutant discharges into the environment due to increasing industrial and agricultural activities is a rising threat for human health and a biggest concern for environmental health globally. Several synthetic chemicals, categorised as potential environmental endocrine-disrupting chemicals (EDCs), are evident to affect the health of not only livestock and wildlife but also human. In recent years, human exposure to environmental EDCs has received increased awareness due to their association with altered human health as documented by several epidemiological and experimental studies. EDCs are associated with deleterious effects on male and female reproductive health; causes diabetes, obesity, metabolic disorders, thyroid homeostasis and increase the risk of hormone-sensitive cancers. Sewage effluents are a major source of several EDCs, which eventually reach large water bodies and potentially contaminate the drinking water supply. Similarly, water storage material such as different types of plastics also leaches out EDCs in drinking Water. Domestic wastewater containing pharmaceutical ingredients, metals, pesticides and personal care product additives also influences endocrine activity. These EDCs act via various receptors through a variety of known and unknown mechanisms including epigenetic modification. They differ from classic toxins in several ways such as low-dose effect, non-monotonic dose and trans-generational effects. This review aims to highlight the hidden burden of EDCs on human health and discusses the non-classical toxic properties of EDCs in an attempt to understand the magnitude of the exposome on human health. Present data on the environmental EDCs advocate that there may be associations between human exposure to EDCs and several undesirable health outcomes and warrants further human bio-monitoring of EDCs.